Activation of Melanocortin Receptors as a Potential Strategy to Reduce Local and Systemic Reactions Induced by Respiratory Viruses - Lonati, Caterina; Gatti, Stefano; Catania, Anna (Frontiers in Endocrinology, 2020)
The clinical hallmarks of infections caused by critical respiratory viruses consist of pneumonia, which can progress to acute lung injury (ALI), and systemic manifestations including hypercoagulopathy, vascular dysfunction, and endotheliitis. The disease outcome largely depends on the immune response produced by the host. The bio-molecular mechanisms underlying certain dire consequences of the infection partly arise from an aberrant production of inflammatory molecules, an event denoted as “cytokine storm”. Therefore, in addition to antiviral therapies, molecules able to prevent the injury caused by cytokine excess are under investigation. In this perspective, taking advantage of melanocortin peptides and their receptors, components of an endogenous modulatory system that exerts marked anti-inflammatory and immunomodulatory influences, could be an effective therapeutic strategy to control disease evolution. Exploiting the melanocortin system using natural or synthetic ligands can form a realistic basis to counteract certain deleterious effects of respiratory virus infections. The central and peripheral protective actions exerted following melanocortin receptor activation could allow dampening the harmful events that trigger the cytokine storm and endothelial dysfunction while sustaining the beneficial signals required to elicit repair mechanisms. The long standing evidence for melanocortin safety encourages this approach.